Yayasan UMP Smart Project helps 120 school students - MUHAMMAD ZUFLI, ZUHARI (2023)
PEKAN, 21 March 2023 - The Yayasan UMP Smart Project involving 120 Year 6 students from 10 schools around Pekan would improve their ability to gain better understanding, experience and knowledge in instilling interest in learning.